Physical activity and its associated factors among adults with chronic kidney disease in a community setting: A secondary data analysis - Jena Lee; Yujin Suh (PLoS ONE, 2025)
Background Physical activity in patients with chronic kidney disease is important as it helps lowers blood pressure, reduces inflammatory markers, improves cognitive function, and improves health-related quality of life. However, there is a lack of studies accurately assess physical activity levels in this population. Objective This study aimed to examine the characteristics of chronic kidney disease patients across eGFR stages, assess the proportion of Korean adults with chronic kidney disease meeting recommended physical activity levels, and identify the factors associated with meeting the weekly physical activity recommendation. Methods We conducted a secondary analysis of data from the 2016–2020 Korean National Health and Nutrition Examination Survey. Descriptive statistics and logistic regression were used to examine physical activity patterns and associated factors. Results Among CKD patients, 79.5% engaged in insufficient physical activity. Factors significantly associated with sufficient activity included sex, smoking status, activity limitation, and eGFR. Conclusions Tailoring physical activity interventions is crucial, considering the patient’s clinical condition, physical performance, and demographic factors.